2022
DOI: 10.3390/cells12010019
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light Treatment of Titanium Microfiber Scaffolds Enhances Osteoblast Recruitment and Osteoconductivity in a Vertical Bone Augmentation Model: 3D UV Photofunctionalization

Abstract: Vertical bone augmentation to create host bone prior to implant placement is one of the most challenging regenerative procedures. The objective of this study is to evaluate the capacity of a UV-photofunctionalized titanium microfiber scaffold to recruit osteoblasts, generate intra-scaffold bone, and integrate with host bone in a vertical augmentation model with unidirectional, limited blood supply. Scaffolds were fabricated by molding and sintering grade 1 commercially pure titanium microfibers (20 μm diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Thus, such surface texture-induced microenvironments with stagnated and concentrated blood and proteins may explain the successful, contact osteogenesis or osseointegration. The effects of hydrophilic titanium surfaces on the recruitment of blood, proteins, and cells have been reported extensively [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. The present study has revealed that a similar effect can occur by surface texturing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, such surface texture-induced microenvironments with stagnated and concentrated blood and proteins may explain the successful, contact osteogenesis or osseointegration. The effects of hydrophilic titanium surfaces on the recruitment of blood, proteins, and cells have been reported extensively [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. The present study has revealed that a similar effect can occur by surface texturing.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, UV treatment removes a pellicle of hydrocarbons from titanium surfaces that accumulates over time [41,48,[67][68][69][70][71][72][73][74][75][76][77]. As a result, hydrophobic, hydrocarbon-contaminated titanium surfaces become superhydrophilic, and decarbonized, pellicle-free titanium surfaces recruit more osteogenic cells [67], promote and strengthen cellular attachment [78,79], and the density/proliferation of cells [80] and other cellular phenotypes is increased [50]. Blood and protein recruitment is also enhanced around pellicle-free, superhydrophilic implants in in silico simulation.…”
Section: Introductionmentioning
confidence: 99%